1991
DOI: 10.1007/bf01756592
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of liposomes containing synthetic bacterial cell wall analogues for tumoricidal activation of monocytes and macrophages

Abstract: We examined the activation to the tumoricidal state of normal mouse peritoneal exudate macrophages, bone marrow macrophages, and human blood monocytes by liposomes containing either lipophilic muramyl tripeptide (CGP 19,835) or a new synthetic analogue of lipoprotein from gram-negative bacteria outer wall, CGP 31,362, or combinations of the two. The superiority of liposomes containing the synthetic lipopeptide over liposomes containing lipophilic muramyl tripeptide for in vitro activation of monocytes and macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Several studies demonstrated that IFN-γ synergizes with MTP-PE to increase tumoricidal activity and to induce secretion of cytokines [20,23,[28][29][30][31]. We found that MTP-PE synergizes with IFN-γ in inducing tumor killing by human macrophages, and augmenting secretion of TNF-α and IL-1β ( Fig.…”
Section: Preclinical Studies and Animal Trialsmentioning
confidence: 60%
“…Several studies demonstrated that IFN-γ synergizes with MTP-PE to increase tumoricidal activity and to induce secretion of cytokines [20,23,[28][29][30][31]. We found that MTP-PE synergizes with IFN-γ in inducing tumor killing by human macrophages, and augmenting secretion of TNF-α and IL-1β ( Fig.…”
Section: Preclinical Studies and Animal Trialsmentioning
confidence: 60%
“…"In situ" is regarded as liposomes that are formed before clinical use [90]. The commercial product of Mepacthas adopted this method for production.…”
Section: In Situ Preparation Of Liposomesmentioning
confidence: 99%
“…There is a long-standing interest in liposomal muramyl (tri) peptides for inducing immune activation (69,70). Recently, renewed interest in MDP sparked, as it was shown to induce a state of DC hyperactivity, when combined with TLR ligands (55,56).…”
Section: Discussionmentioning
confidence: 99%